Auditory EEG Decoding Challenge for ICASSP 2024 - Lies Bollens; Corentin Puffay; Bernd Accou; Jonas Vanthornhout; Hugo Van Hamme; Tom Francart (IEEE Open Journal of Signal Processing)
This paper describes the auditory EEG challenge, organized as one of the Signal Processing Grand Challenges at ICASSP 2024. The challenge provides electroencephalogram (EEG) recordings of 105 subjects who listened to continuous speech, as audiobooks or podcasts, while their brain activity was recorded. The challenge consists of two tasks that relate EEG signals to the presented speech stimulus. The first task, called match-mismatch, is to determine which of five speech segments induced a given EEG segment. The second task, called regression, is to reconstruct the Mel spectrogram from the EEG. EEG recordings of 85 subjects were provided as a training set so that challenge participants could train their models on a relatively large dataset. The remaining 20 subjects were used as held-out subjects for the evaluation step of the challenge.